Peripheral Arterial Disease Among First Nations People with Diabetes in Ontario, Canada: Linkage of Population-Level Healthcare Data - Shah, Baiju R; Frymire, Eliot; Jones, Carmen R; Khan, Shahriar; Slater, Morgan; Walker, Jennifer D; Green, Mike (International Journal of Population Data Science, 2020)
Introduction Indigenous people worldwide are overrepresented and adversely effected by diabetes. Peripheral arterial disease and amputation are among the most feared complications of diabetes, leading to profound impacts on patients’ quality of life. This study linked population-level healthcare data to assess the risk of peripheral arterial disease among First Nations people in Ontario with diabetes. Objectives and Approach We linked individual-level population-based healthcare administrative datasets with the Indian Register. The latter provides information on all registered or Status First Nations people in Canada. We compared First Nations people with diabetes with other people in Ontario with diabetes . Age and sex-adjusted rates peripheral revascularization procedures and lower-extremity amputations were calculated for each 12-month period from April 1, 1995, to March 31, 2015. Mortality among those with amputation was determined. Results First Nations people received revascularization procedures at a comparable rate to other people in Ontario. However, they had lower-extremity amputations at 3- to 5-times the frequency of other Ontario residents. First Nations people had increased mortality after lower-extremity amputation (adjusted hazard ratio 1.15, 95% confidence interval 1.05 to 1.26), with median survival of only 3.5 years. Conclusion / Implications First Nations people with diabetes in Ontario had a comparable rate of revascularization but a markedly increased risk for lower-extremity amputation compared to other people in Ontario. This discordance suggests that peripheral arterial disease may be underdiagnosed or undertreated among First Nations people in Ontario, and demonstrates an important health inequity faced by First Nations people.